An enquiry into potential graduate entrepreneurship - Birch, Chris; Lichy, Jessica; Mulholland, Gary; Kachour, Maher (The Journal of management development, 2017)
Purpose In today’s global economy, high in talent but low in growth, the capability and skills mismatch between the output of universities and the demands of business has escalated to a worrying extent for graduates. Increasingly, university students are considering alternatives to a lifetime of employment, including their own start-up, and becoming an entrepreneur. The literature indicates a significant disconnect between the role and value of education and healthy enterprising economies, with many less-educated economies growing faster than more knowledgeable ones. Moreover, theory concerning the entrepreneurial pipeline and entrepreneurial ecosystems is applied to graduate entrepreneurial intentions and aspirations. The paper aims to discuss these issues. Design/methodology/approach Using a large-scale online quantitative survey, this study explores graduate “entrepreneurial intention” in the UK and France, taking into consideration personal, social and situational factors. The results point to a number of factors that contribute to entrepreneurial intention including social background, parental occupation, gender, subject of study and nationality. The study furthers the understanding of and contributes to the extant literature on graduate entrepreneurship. It provides an original insight into a topical and contemporary issue, raising a number of research questions for future study. Findings For too long, students have been educated to be employees, not entrepreneurs. The study points strongly to the fact that today’s students have both willingness and intention to become entrepreneurs. However, the range of pedagogical and curriculum content does not correspond with the ambition of those who wish to develop entrepreneurial skills. There is an urgent need for directors of higher education and pedagogues to rethink their education offer in order to create a generation of entrepreneurs for tomorrow’s business world. The challenge will be to integrate two key considerations: how to create a business idea and how to make it happen practically and theoretically. Clearly, change in the education product will necessitate change in the HE business model. Research limitations/implications The data set collected was extensive (c3500), with a focus on France and the UK. More business, engineering and technology students completed the survey than others. Further research is being undertaken to look at other countries (and continents) to test the value of extrapolation of findings. Initial results parallel those described in this paper. Practical implications Some things can be taught, others need nurturing. Entrepreneurship involves a complex set of processes which engender individual development, and are highly personalised. Higher Education Enterprise and Teaching and Learning Strategies need to be cognisant of this, and to develop innovative and appropriate curricula, including assessment, which reflects the importance of the process as much as that of the destination. Social implications The global economy, propelled by the push and pull of technology, is changing at a speed never before seen. This is having profound political, social and economic effects which necessitate fundamental change that we organise ourselves and our activities. Current models and modus operandi are proving increasingly unfit for purpose. Nurturing and encouraging agile mindsets, creativity, supporting the testing of new ideas and ways of doing things and adapting/adopting to innovation are all critical future employability factors. Our future prosperity and well-being will be dependent on creating new learning models. Originality/value This work builds on an extensive literature review coupled with original primary research. The authors originate from a variety of backgrounds and disciplines, and the result is a very challenging set of thoughts, comments and suggestions that are relevant to all higher education institutions, at policy, strategy and operational levels.